The Potential of Extracts Derived from Leaves of Edible Medicinal Plants for Their Antimicrobial and Antioxidant Activities - Napum, Korapin; Suksuwan, Orasa; Supaphon, Preuttiporn (Journal of Advanced Development in Engineering and Science, 2026)
This study aimed to evaluate the antimicrobial and antioxidant activities of ethanolic leaf extracts from four edible medicinal plants: Clerodendrum disparifolium, Ehretia acuminata, Blumea balsamifera, and Strobilanthes crispa. Leaf samples from the four plant species were extracted using ethanol as the solvent. The extracts were tested for antimicrobial activity against eight strains of pathogenic microorganisms: Staphylococcus aureus ATCC25923, Methicillin-Resistant Staphylococcus aureus (MRSA) SK1, Staphylococcus epidermidis, Escherichia coli ATCC25922, Pseudomonas aeruginosa ATCC27853, Acinetobacter baumannii, Candida albicans NCPF3153 and Cryptococcus neoformans ATCC90112 using the colorimetric broth microdilution method. Antioxidant activity and total phenolic content of the extracts were assessed using the DPPH radical scavenging assay and the Folin-Ciocalteu method, respectively. In addition, the chemical composition of bioactive compounds in the extracts was analyzed using Gas Chromatography-Mass Spectrometry (GC-MS).Among the extracts tested, the leaf extract of B. balsamifera exhibited the highest antimicrobial activity, effectively inhibiting the growth of S. aureus, S. epidermidis, and MRSA with a minimum inhibitory concentration (MIC) of 1.024 mg/mL. The extract from B. balsamifera demonstrated the strongest antioxidant activity, with an IC50 value of 0.178 ± 0.10 mg/mL in the DPPH assay. Moreover, it contained the highest total phenolic content, measured at 88.769 ± 10.33 mg gallic acid equivalent/g extract. GC-MS analysis revealed that phytol was the most abundant compound in the extract. These findings indicate that herbal extracts are promising sources of bioactive compounds and provide scientific support for the traditional use of these plants. The results also offer a basis for future investigations into their other biological activities.